2023
DOI: 10.26668/businessreview/2023.v8i2.1106
|View full text |Cite
|
Sign up to set email alerts
|

How Spiritual Leadership Influences Creative Behaviors: the Mediating Role of Workplace Climate

Abstract: Purpose: The aim of this study is to examine the relationship between spiritual leadership and creative behavior with workplace climate as mediating variable in the Jordanian banking.   Theoretical framework: The purpose of this study, which extends the theories of intrinsic motivation and social exchange, is to acquire a deeper knowledge of the mechanisms underlying the relationship between spiritual leadership and innovative workplace behavior.   Design/methodology/approach: The study used quantitative resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 61 publications
0
14
0
Order By: Relevance
“…Thus, constructs of this study possess reliability and convergent validity (Harindranath & Sivakumaran, 2021). Further, we examine for discriminant validity using Fornell & Larcker, (1981) criterion and found that the square root of the AVE values is higher comparing the correlations of a pair of constructs, establishing the discriminant validity (Khaddam et al, 2023) (refer to Table 1). Therefore, our model possesses reliability and validity.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, constructs of this study possess reliability and convergent validity (Harindranath & Sivakumaran, 2021). Further, we examine for discriminant validity using Fornell & Larcker, (1981) criterion and found that the square root of the AVE values is higher comparing the correlations of a pair of constructs, establishing the discriminant validity (Khaddam et al, 2023) (refer to Table 1). Therefore, our model possesses reliability and validity.…”
Section: Resultsmentioning
confidence: 97%
“…Transformational leaders can establish positive relationships with their members and inspire them to perform better by sharing knowledge, resources, and expertise. When leaders focus on this approach, employees tend to put greater effort and energy into performing tasks more effectively (Khaddam, Alzghoul, Khawaldeh, Alnajdawi, & Al-Kasasbeh, 2023). In other words, transformational leaders can motivate their employees to strive for and achieve goals beyond predetermined expectations by transforming their followers' attitudes, beliefs, values, and needs (Udin, 2023).…”
Section: Literature and Hypotheses Transformational Leadership (Tfl)mentioning
confidence: 99%
“…The significance of leadership in propelling organizational success cannot be overstated, as its influence permeates every aspect of the organization Khaddam et al, 2023). Bass and Bass (2008) have highlighted the correlation between effective leadership and positive employee satisfaction, increased productivity, and improved financial results.…”
Section: Introductionmentioning
confidence: 99%